2017
DOI: 10.1186/s12711-017-0309-2
|View full text |Cite
|
Sign up to set email alerts
|

Metafounders are related to F st fixation indices and reduce bias in single-step genomic evaluations

Abstract: Background Metafounders are pseudo-individuals that encapsulate genetic heterozygosity and relationships within and across base pedigree populations, i.e. ancestral populations. This work addresses the estimation and usefulness of metafounder relationships in single-step genomic best linear unbiased prediction (ssGBLUP).ResultsWe show that ancestral relationship parameters are proportional to standardized covariances of base allelic frequencies across populations, such as fixation indexes. These covariances o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 53 publications
1
77
0
Order By: Relevance
“…This assumption can be removed using the metafounder approach [ 21 ], which postulates that the pedigree-based additive relationship between any pair of founders is equal to a positive parameter (from 0 to 2) that summarizes the situation of the pedigree base in reference to the genomic base [ 10 ]. This parameter can be estimated from genomic data [ 22 ], and represents the homozygosity across founders in the pedigree that would yield observed genomic relationships in , where is computed as the cross-product with containing {− 1, 0, 1} values. Furthermore, Garcia-Baccino et al [ 22 ] showed that the value of is relative to a theoretical genomic base that displays maximum variability at each marker locus (allelic frequencies 0.5), thus giving rise by drift to the pedigree base and to differentiation of frequencies in the genotyped population.…”
Section: Methodsmentioning
confidence: 99%
“…This assumption can be removed using the metafounder approach [ 21 ], which postulates that the pedigree-based additive relationship between any pair of founders is equal to a positive parameter (from 0 to 2) that summarizes the situation of the pedigree base in reference to the genomic base [ 10 ]. This parameter can be estimated from genomic data [ 22 ], and represents the homozygosity across founders in the pedigree that would yield observed genomic relationships in , where is computed as the cross-product with containing {− 1, 0, 1} values. Furthermore, Garcia-Baccino et al [ 22 ] showed that the value of is relative to a theoretical genomic base that displays maximum variability at each marker locus (allelic frequencies 0.5), thus giving rise by drift to the pedigree base and to differentiation of frequencies in the genotyped population.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy for such cases could be improved by taking into account the different base populations by implementing the GLS_Sparse method with genetic groups. This could be done by replacing the vector 1 in the different formulae by a matrix Q that contains the expected fraction of each genetic group for each geno- with μ i being a vector of estimates of base allele frequencies for all genetic groups (Gengler et al, 2007;VanRaden, 2008;Makgahlela et al, 2013;Garcia-Baccino et al, 2017). .…”
Section: Discussionmentioning
confidence: 99%
“…The GLS equivalent uses the method proposed by McPeek et al (2004) and implemented by Strandén et al (2017) and Garcia-Baccino et al (2017) in which for the ith SNP…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations